Przemiany profilu partnerki w stereotypie dziewczyny - Wacławek, Maria (Postscriptum Polonistyczne, 2020)
The article aims at presenting part of the research that has been done on the stereotypes of a ‘girlfriend’ (Polish: ‘dziewczyna’). The research is based on letters published in Polish magazines for teenagers at the end of the communist regime and in the first decades of the 21st century. Partner profiling is an important element of the reconstructed stereotype. The description follows analysis of the traditional image of a female partner, which is based on an analysis of Polish proverbs. The research reveals many elements typical of the traditional model, especially the culturally accepted passive attitude of girls (especially in the Polish People’s Republic period). Modification of the model appears in a later period: freedom of customs, sexual awareness, and behaviour that is more liberated (based on letters written from the beginning of the 21st century).